Corrosion mechanism of Pseudomonas stutzeri on X80 steel subjected to Desulfovibrio desulfuricans under elastic stress and yield stress. (15th May 2023) - Fu, Qi; Wei, Boxin; Xu, Jin; Qin, Qingyu; Bai, Yunlong; Yu, Changkun; Sun, Cheng
Abstract: Biocorrosion of X80 steel for Desulfovibrio desulfuricans and Pseudomonas stutzeri under elastic stress and yield stress was performed in neutral soil environment. Electrochemical results showed that yield stress resulted in higher corrosion rate for X80 specimens compared to elastic stress. When both yield stress and Desulfovibrio desulfuricans were applied to the specimens, the surface pit diameter and depth of the X80 specimens were the largest of all conditions and numerous secondary pits appeared at the bottom of primary pits. However, the introduction of Pseudomonas stutzeri significantly reduced the corrosion caused by Desulfovibrio desulfuricans . Highlights: Yield stress causes more serious corrosion damage than elastic stress. SRB and yield stress synergistically lead to the formation of secondary pits. The synergistic effect of SRB and stress is greater than Pseudomonas stutzeri . Pseudomonas stutzeri can significantly reduce the pit depth caused by SRB.